(untitled) (Journal of Engineering, 2025)
A new model equation has been constructed to estimate the liquid limit value, using the rapid one point method. Data processing was carried out in Microsoft Excel and SPSS, visualizing and using 6,210 theoretical trial points, which resulted from 135 samples along the actual flow index line, with the number of blows varying from 5 to 50 with an interval of unity. The model has two correction factors (CF), both of which are functions of the number of blows at the trial point in the test. The first CF is applied to the trial moisture content, while the second CF is applied to the previously estimated liquid limit. This technique was checked against real data points. For estimating the liquid limit for a large range of blows (N) from 10 to 45 the model achieved a high R2 value of over 0.99. It also has a low RMSE of 3.8 for the set of 6,210 theoretical points and 2.2 for 220 actual points. In this research, the flexibility of the model is crucial as it provides a wider range of blows from 10 to 45, unlike the ASTM procedure for which there are set requirements that state the amount of blows to be between 20 and 30.